Repetitive sequences: The hidden diversity of heterochromatin in prochilodontid fish - Terêncio, Maria Leandra; Schneider, Carlos Henrique; Gross, Maria Claudia; Carmo, Edson Júnior do; Nogaroto, Viviane; Almeida, Mara Cristina de; Artoni, Roberto Ferreira; Vicari, Marcelo Ricardo; Feldberg, Eliana (Comparative Cytogenetics, 2015)
The structure and organization of repetitive elements in fish genomes are still relatively poorly understood, although most of these elements are believed to be located in heterochromatic regions. Repetitive elements are considered essential in evolutionary processes as hotspots for mutations and chromosomal rearrangements, among other functions - thus providing new genomic alternatives and regulatory sites for gene expression. The present study sought to characterize repetitive DNA sequences in the genomes of Semaprochilodus insignis (Jardine & Schomburgk, 1841) and Semaprochilodus taeniurus (Valenciennes, 1817) and identify regions of conserved syntenic blocks in this genome fraction of three species of Prochilodontidae (S. insignis, S. taeniurus, and Prochilodus lineatus (Valenciennes, 1836) by cross-FISH using Cot-1 DNA (renaturation kinetics) probes. We found that the repetitive fractions of the genomes of S. insignis and S. taeniurus have significant amounts of conserved syntenic blocks in hybridization sites, but with low degrees of similarity between them and the genome of P. lineatus, especially in relation to B chromosomes. The cloning and sequencing of the repetitive genomic elements of S. insignis and S. taeniurus using Cot-1 DNA identified 48 fragments that displayed high similarity with repetitive sequences deposited in public DNA databases and classified as microsatellites, transposons, and retrotransposons. The repetitive fractions of the S. insignis and S. taeniurus genomes exhibited high degrees of conserved syntenic blocks in terms of both the structures and locations of hybridization sites, but a low degree of similarity with the syntenic blocks of the P. lineatus genome. Future comparative analyses of other prochilodontidae species will be needed to advance our understanding of the organization and evolution of the genomes in this group of fish. © Maria L. Terencio et al.